Modified Cantwel-Ransley Reconstruction of Continent Penile Epispadias In Children: A Case Report - Nadhir, Ahmad; Tarmono, Tarmono (Folia Medica Indonesiana, 2021)
Epispadias as an isolated embryologic defect is a rare anomaly, with an incidence of 1 in 117.000 males. Isolated epispadias with continence is a very rare condition comprising less than 10% of all epispadias cases. Epispadias is a closure defect of the dorsal wall of the urethra. The biggest challenges for epispadias treatment are creating adequate penile length, straightening the severely curved penis, and creating a penopubic angle for allowing comfortable penetration of the penis. An 11-year-old boy underwent surgery for his continent penile epispadias in Dr. Soetomo General Academic Hospital. The surgical technique chosen for this patient was Modified Cantwell-Ransley repair. The dressing was opened on the 3rd day after the operation. The urethral catheter was removed on the 10th day. The patients underwent regular follow-up examinations for 6 months and were evaluated for subjective and objective outcomes. There was no post-operative fistula or urethral narrowing requiring urethral dilatation. The Uroflowmetry and post voiding residual ultrasound result was good. The cosmetic appearance of the penis was satisfying. Outcomes related to sexual activity were not evaluated because the patient had no sexual activity yet.